Applied statistics for business and research - Agbayani, Victor A. E. (Quezon City : AFA Publications, 1994)
The objective of this book is to teach readers of diverse disciplines, not necessarily mathematical, the application of basic statistical methods through examples in the Philippine context. For this practical purpose, discussions of concepts are made concise, and mathematical derivations give way to the generous use of examples as a teaching tool.
Chapter 1. organizing data -- Chapter 2. measures of location -- Chapter 3. measures of variability -- Chapter 4. probability -- Chapter 5. special probability distributions -- Chapter 6. estimation -- Chapter 7. testing hypotheses -- Chapter 8. the chi-square test -- Chapter 9. simple linear regression.
Includes bibliographical references and index.
Keywords: COMMERCIAL STATISTICS; RESEARCH STATISTICS